(untitled) (Biological Sciences - PJSIR, 2025)
The grain yield in greater amount under water stress has always been the prime objective of most of the studies pertaining to the identification of potential genotypes of wheat tested for morpho-yield and physiological traits. Selection of genotypes was thus based on their mean performance under water stress conditions imposed on tillering stages. Eighteen popular wheat varieties were evaluated for days to 75% heading, days to 75% maturity, plant height, tillers/plant, spike length, spikelets/spike, grains/spike, seed index, grain yield/plant, biological yield/plant and harvest index. The wheat varieties, viz., Bhittai, Marvi-2000, NIA-Sarang, TD-1, NIA-Sunder, Inqilab and Khirman, were identified as tolerant to water stress. Grain yield per plant was positively significant associated with its related traits in stress and water stress environments. These traits should be improved through simple selection in lateral generations of segregation populations.